Sistem Pembakaran Limbah Padat Industri Percetakan - Rofienda Rofienda; Wuryanto Wuryanto; Moh T S (Jurnal Kimia dan Kemasan, 2000)
The optimum combustion of solid waste from printing industry utilizing "Combustion Gas Cleaning System" unit is achieved at temperature 750 "C - 780 °C, 1,2 - 1,5 mm Hg/aqua pressure with diesel  consumption at 5. 7 kg/hr. It was found that the combustion process could reduce the solid waste total weight and volume up to 60 %. While the content of toxic materials and hazardous materials remain unchanged. Analysis on the weight of "heavy metal" was conducted prior to and after the combustion. The analysis comes up with result that the content of heavy metal in the waste is largerthan before the combustion. Thus means, that the content of heavy metal in solid waste is not affected by the above combustion process. The weight and volume of waste is greatly decreased, while heavy metal component is concentrated in residue.